Agrobacterium infection and plant defense—transformation success hangs by a thread - Pitzschke, Andrea (Frontiers in Plant Science, 2013)
The value of Agrobacterium tumefaciens for plant molecular biologists cannot be appreciated enough. This soil-borne pathogen has the unique capability to transfer DNA into plant systems. Gene transfer involves both bacterial and host factors, and it is the orchestration of these factors that determines the success of transformation. Some plant species readily accept integration of foreign DNA, while others are recalcitrant. The timing and intensity of the microbially activated host defense repertoire sets the switch to “yes” or “no”. This repertoire is comprised of the specific induction of mitogen-activated protein kinases, defense gene expression, production of reactive oxygen species and hormonal adjustments. Agrobacterium tumefaciens abuses components of the host immunity system; it mimics plant protein functions and manipulates hormone levels to bypass or override plant defenses. A better understanding of the ongoing molecular battle between agrobacteria and attacked hosts paves the way towards developing transformation protocols for recalcitrant plant species. This review highlights recent findings in agrobacterial transformation research conducted in diverse plant species. Efficiency-limiting factors, both of plant and bacterial origin, are summarized and discussed in a thought-provoking manner.